Finding Chika : a little girl, an earthquake, and the making of a family - Albom, Mitch, 1958- (New York : Harper, an imprint of HarperCollins Publishers, 2019)
Chika Jeune was born three days before the devastating earthquake that decimated Haiti in 2010. She spent her infancy in a landscape of extreme poverty, and when her mother died giving birth to a baby brother, Chika was brought to The Have Faith Haiti Orphanage that author Mitch Albom operates in Port Au Prince. Chika's arrival makes a quick impression. Brave and self-assured, even as a three-year-old, she delights the other kids and teachers. But at age five, Chika is suddenly diagnosed with something a doctor there says, "No one in Haiti can help you with." Albom and his wife, Janine, bring Chika to Detroit, hopeful that American medical care will soon grant her a healthy return to her homeland. Instead, Chika becomes a permanent part of the Alboms' lives, as they embark on a two-year, around-the-world journey to find a cure.
Keywords: Jeune, Chika; Albom, Mitch; Orphans -- Haiti -- Biography; Families